Multi-stage bed high-load low-resistance catalyst for maleic anhydride prepared by butane process and preparation method of multi-stage bed high-load low-resistance catalyst

By introducing cocatalytic metal salt into Catalyst A and diluting and combining with an inert magnetic ring, a multi-stage bed high-load low-resistance butane method classic anhydride catalyst was prepared, which solved the activity and selectivity of existing catalysts under high load conditions. The problem of insufficient results has achieved efficient and low-cost catalytic effects.

CN119455999APending Publication Date: 2025-02-18CHANGZHOU XINRI CATALYST CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411261868.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing butane catalysts have low catalytic activity and selectivity under high load conditions. Increased bed resistance leads to increased energy consumption and cost, and cannot meet the requirements of high inlet concentration and low bed resistance.

Method used

By introducing a cocatalytic metal salt into catalyst A and diluting and combining with an inert magnetic ring, a multi-stage bed high load low resistance butane method of a manic anhydride catalyst was prepared.

Benefits of technology

The high load and low resistance characteristics of the catalyst are achieved, which reduces energy consumption and costs, while increasing production capacity and meeting market demand.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of maleic anhydride production, in particular to a multi-stage bed high-load low-resistance catalyst for maleic anhydride produced by a butane process and a preparation method of the catalyst. The method comprises the following steps: step 1, (1) sequentially adding vanadium pentoxide and co-catalytic metal salt into a mixed solvent of isobutanol and benzyl alcohol; controlling the temperature to be 100-130 DEG C, and dropwise adding phosphoric acid within 1-2 hours at a constant speed; continuously carrying out reflux reaction for 10-20 hours; cooling and filtering; filtering to obtain a filter cake; (2) sequentially drying and roasting the filter cake to obtain an active precursor; 2, (1) granulating the active precursor, adding graphite, uniformly mixing, and carrying out compression molding to obtain a catalyst A semi-finished product; (2) activating the catalyst A semi-finished product in an oxygen-containing atmosphere to obtain a catalyst A; and 3, diluting and compounding the catalyst A and an inert magnetic ring to obtain the butane-process maleic anhydride catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of maleic anhydride production, in particular to a multi-stage bed high-load low-resistance butane process maleic anhydride catalyst and a preparation method thereof. Background Art

[0002] The preparation of maleic anhydride by butane method is an important chemical reaction; its products can be used not only in synthetic resins, lubricating oils and other process products, but also in the technical fields of medicine, food and so on, and are widely used. Among them, one of the key technologies for the preparation of maleic anhydride by butane method is catalyst technology, which affects the energy consumption, yield and other aspects of the overall reaction process.

[0003] In the prior art, there is a tendency to pursue high-load and low-resistance catalyst technology in order to reduce energy consumption and increase production capacity. The existing VPO catalyst has the disadvantages of low catalytic activity and catalytic selectivity and cannot be applied to high loads. In practical applications, as the height of the catalyst bed increases, the bed resistance also increases, the catalyst performance also decreases, and the feed concentration cannot be increased, which also leads to an increase in energy consumption despite the increase in production capacity. Although in some studies, in order to increase production capacity, the purpose is achieved by increasing the pipe diameter and the number of tubes, but it does not fundamentally change the problem, and the energy consumption and cost of the device have not been reduced. At the same time, the existing catalyst is only suitable for single-layer or double-layer catalysts in the device, which cannot meet the requirements of high inlet concentration and low bed resistance in the device.

[0004] In summary, it is of great significance to solve the above problems and prepare a multi-stage bed high-load low-resistance butane process maleic anhydride catalyst to meet market demand. Summary of the invention

[0005] The object of the present invention is to provide a multi-stage bed high-load low-resistance butane process maleic anhydride catalyst and a preparation method thereof, so as to solve the problems raised in the above background technology.

[0006] In order to solve the above technical problems, the present invention provides the following technical solution: a method for preparing a multi-stage bed high-load low-resistance butane process maleic anhydride catalyst, comprising the following steps: Step 1: (1) adding vanadium pentoxide and a catalytic metal salt to a mixed solvent of isobutyl alcohol and benzyl alcohol in sequence; controlling the temperature to 100-130°C, and uniformly adding phosphoric acid dropwise within 1-2 hours; continuing the reflux reaction for 10-20 hours; cooling and filtering; obtaining a filter cake; (2) drying and calcining the filter cake in sequence to obtain an active precursor; Step 2: (1) granulating the active precursor, adding graphite and mixing evenly, and pressing to form a catalyst A semi-finished product; (2) activating the catalyst A semi-finished product in an oxygen-containing atmosphere to obtain catalyst A; Step 3: dilute and compound the catalyst A with an inert magnetic ring to obtain a butane-process maleic anhydride catalyst.

[0007] More optimally, the active precursor includes the following raw materials by weight: 400-420 parts of vanadium pentoxide, 18-20 parts of catalytic metal salt, 2400-2600 parts of isobutanol, 480-500 parts of benzyl alcohol, and 480-500 parts of phosphoric acid; The metal type of the catalytic metal salt includes at least one of magnesium, aluminum and calcium.

[0008] More optimally, the dilution and compounding ratio between catalyst A and inert magnetic ring is 1:1~2:1.

[0009] More optimally, in step 1 (2), the specific process is: drying the filter cake at 100-130°C for 18 hours, and then calcining at 300-350°C for 6 hours to obtain an active precursor.

[0010] More optimally, in the catalyst A semi-finished product, the amount of graphite added accounts for 2-5wt% of the catalyst A semi-finished product.

[0011] More optimally, the particle size of the active precursor granulation is 10-40 mesh; the catalyst A is a hollow cylinder with an outer diameter of 5-7 mm, a height of 5-7 mm, and an inner diameter of 2.5-4 mm.

[0012] More optimally, in step 2 (2), the specific process is: placing the semi-finished product of catalyst A in an atmosphere with an oxygen content of 10% to 14%, controlling the temperature to 460 to 480° C. for activation for 10 to 18 hours; obtaining catalyst A.

[0013] Preferably, antimony oxide / graphene is added to the active precursor; the specific process comprises the following steps: (1) adding vanadium pentoxide and a catalytic metal salt to a mixed solvent of isobutyl alcohol and benzyl alcohol in sequence; adding antimony oxide / graphene and dispersing them uniformly; controlling the temperature to 100-130° C. and uniformly adding phosphoric acid dropwise within 1-2 hours; continuing the reflux reaction for 10-20 hours; cooling and filtering; obtaining a filter cake; (2) drying and calcining the filter cake in sequence to obtain an active precursor; The added amount of antimony oxide / graphene accounts for 0.8-1wt% of vanadium pentoxide.

[0014] More optimally, the preparation method of antimony oxide / graphene is as follows: (1) dissolving yttrium nitrate and antimony trichloride in anhydrous ethanol at a molar ratio of 1:8-12 respectively to obtain yttrium solution and antimony solution; dropping the yttrium solution into the antimony solution, stirring evenly, adding ammonia water, adjusting the pH to 7-10 with acid, stirring at room temperature for 2-4 hours; filtering, washing, and drying; calcining it at 300-600°C for 2-3 hours to obtain antimony oxide; (2) ultrasonically dispersing antimony oxide in ethylene glycol, adding graphene oxide and stirring evenly; placing it at 120-140°C for hydrothermal reaction for 8-12 hours, washing, drying, and grinding; obtaining antimony oxide / graphene; wherein the mass ratio of antimony oxide to graphene oxide is 1:3-5.

[0015] Compared with the prior art, the present application has the following beneficial effects: In the scheme, a butane process maleic anhydride catalyst is obtained by introducing a catalytic metal salt into catalyst A and using an inert magnetic ring in combination with catalyst A for dilution and compounding. The catalyst can be used in a multi-stage bed and has the advantages of high load and low resistance. It can increase production capacity on the basis of reducing energy consumption and cost to meet market demand.

[0016] Among them, in order to solve the bed resistance problem faced by the increase of the catalyst bed, the catalyst A is diluted and prepared by the inert magnetic ring; thereby reducing the resistance and increasing the load; however, the catalytic activity will decrease after dilution; therefore, in order not to affect the catalytic rate; in the scheme, a catalytic metal salt including at least one of magnesium, aluminum, and calcium is introduced into the catalyst A to improve the activity and selectivity of the butane process maleic anhydride catalyst, thereby compensating for the negative impact caused by the dilution.

[0017] Among them, the catalytic metal salt is highly dispersed in (VO)2P2O7 in the form of phosphate in Catalyst A, making its grain size larger and its specific surface area higher; at the same time, its introduction has a good selective oxidation function, making the selective oxidation active temperature lower; in turn, effectively improving the activity and selectivity of the catalyst.

[0018] In a further scheme, in order to further enhance the activity and selectivity of the butane process maleic anhydride catalyst, antimony oxide / graphene is further introduced into catalyst A in the scheme.

[0019] Among them, graphene has a high specific surface area and can act as a structure director and electron promoter in the catalyst; due to its large specific surface area, it can increase the active sites; at the same time, it can promote electron transfer and reduce the activation energy of the reaction; at the same time, its introduction can improve the stability of the catalyst and optimize the electronic structure of the catalyst; and the further loaded antimony oxide can affect the nucleation and growth of (VO)2P2O7, which helps to improve the active phase and inhibit the δ-VOPO4 phase, thereby improving the selective oxidation; at the same time, metal yttrium is further doped in the antimony oxide, and its introduction can increase the crystalline oxygen on the catalyst surface, thereby changing the surface acidity of the catalyst; thereby, the catalytic activity and selectivity of the butane process maleic anhydride catalyst are effectively improved. DETAILED DESCRIPTION

[0020] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] It should be noted that the purchase manufacturers of all raw materials involved in the present invention are not subject to any special restrictions and exemplarily include: in the following embodiments, the product number of graphene oxide is M33420, and the brand is Myrel; the material of the inert magnetic ring is ceramic.

[0022] Preparation of antimony oxide / graphene: (1) Dissolve 0.38g of yttrium nitrate hexahydrate and 1.85g of antimony trichloride in anhydrous ethanol to obtain a 10wt% yttrium solution and a 10wt% antimony solution; drop the yttrium solution into the antimony solution, stir evenly, add excess ammonia water, and precipitate completely; add hydrochloric acid to adjust the pH to 9.3, ultrasonically disperse for 10 minutes, and stir at room temperature for 3 hours; filter, wash, and dry; calcine it at 300°C for 2 hours to obtain antimony oxide; it can be scaled up in proportion; (2) Ultrasonic disperse 1g of antimony oxide in 20g of ethylene glycol, add 5g of graphene oxide and stir evenly; place it at 140°C for hydrothermal reaction for 10 hours, wash, dry, and grind; obtain antimony oxide / graphene; it can be scaled up in proportion.

[0023] Preparation of Catalyst A: (1) In a glass reactor in the laboratory, 2500g of isobutanol, 500g of benzyl alcohol, 417g of vanadium pentoxide and 19.5g of magnesium carbonate are added in sequence, the stirred reactor is started, stirred and heated, and the temperature is controlled to be 120°C. After the temperature reaches the required temperature, 490g of phosphoric acid is added at a uniform rate, and the phosphoric acid is added within 1 hour, and then the reactor is started to reflux, and the reflux reaction time is 20 hours. After the reaction is completed, the filter cake is cooled and filtered to obtain a filter cake, which is dried at 100°C for 18 hours; and calcined at 300°C for 6 hours to obtain an active precursor; (2) The active precursor is granulated, sieved through a 40-mesh sieve, mixed with 3wt% of graphite, pressed into tablets, and activated in an atmosphere furnace with an oxygen content of 12% at a temperature of 460°C for 18 hours, and cooled to obtain catalysts A of different specifications; the preparation can be expanded.

[0024] Examples 1 to 20: Catalyst A with an outer diameter of 5.6 mm and a height of 5.6 mm, and an inert magnetic ring with an outer diameter of 5.6 mm and a height of 5.6 mm as a quantitative quantity, and examples executed with different total bed heights, different dilution level compounding ratios, different bed height ratios, and different bed heights as variables; the details are as follows: Example 1: Catalyst A is loaded as T1 into a tube array with a tube length of 7000 mm. The bed height of T1 is the total bed height, and the bed height is 5500 mm. The catalytic performance is evaluated and tested to obtain test result A1.

[0025] Example 2: Catalyst A is loaded as T1 into a tube array with a tube length of 7000 mm. The bed height of T1 is the total bed height, and the bed height is 6000 mm. The catalytic performance is evaluated and tested to obtain test result A2.

[0026] Example 3: Catalyst A is loaded as T1 into a tube array with a tube length of 7000 mm. The bed height of T1 is the total bed height, and the bed height is 6200 mm. The catalytic performance is evaluated and tested to obtain test result A3.

[0027] Example 4: Take catalyst A as T1 and load it into a tube array with a tube length of 7000 mm, and the bed height of T1 is 2750 mm; take catalyst A and inert magnetic rings in a volume ratio of 1:1 and dilute and compound to form T2 and load it into the tube array, and the bed height of T2 is 2750 mm; the ratio of the bed height of T1 to the bed height of T2 is 1:1, and the total bed height is 5500 mm. The catalytic performance is evaluated and tested, and the test result A4 is obtained.

[0028] Example 5: Take catalyst A as T1 and load it into a tube array with a tube length of 7000 mm, and the bed height of T1 is 2750 mm; take catalyst A and inert magnetic rings in a volume ratio of 2:1 to dilute and compound to form T2 and load it into the tube array, and the bed height of T2 is 2750 mm; the ratio of the bed height of T1 to the bed height of T2 is 1:1, and the total bed height is 5500 mm. The catalytic performance is evaluated and tested, and the test result A5 is obtained.

[0029] Example 6: Take catalyst A as T1 and load it into a tube array with a tube length of 7000 mm, and the bed height of T1 is 3670 mm; take catalyst A and inert magnetic rings in a volume ratio of 1:1 to dilute and compound to form T2, and load it into the tube array, and the bed height of T2 is 1830 mm; the ratio of the bed height of T1 to the bed height of T2 is 2:1, and the total bed height is 5500 mm. The catalytic performance is evaluated and tested, and the test result A6 is obtained.

[0030] Example 7: Catalyst A is taken as T1 and loaded into a tube array with a tube length of 7000 mm, and the bed height of T1 is 3670 mm; Catalyst A and inert magnetic rings are diluted and compounded in a volume ratio of 2:1 to form T2, which is loaded into the tube array, and the bed height of T2 is 1830 mm; the ratio of the bed height of T1 to the bed height of T2 is 2:1, and the total bed height is 5500 mm. The catalytic performance is evaluated and tested, and the test result A7 is obtained.

[0031] Example 8: Take catalyst A as T1 and load it into a tube array with a tube length of 7000 mm, and the bed height of T1 is 2750 mm; take catalyst A and inert magnetic rings at a volume ratio of 2:1 to dilute and compound to form T2, and load it into the tube array, and the bed height of T2 is 1375 mm; take catalyst A and inert magnetic rings at a volume ratio of 1:1 to dilute and compound to form T3, and load it into the tube array, and the bed height of T3 is 1375 mm; the ratio of the bed height of T1, the bed height of T2 and the bed height of T3 is 2:1:1, and the total bed height is 5500 mm. The catalytic performance is evaluated and tested, and the test result A8 is obtained.

[0032] Example 9: Take catalyst A as T1 and load it into a tube array with a tube length of 7000 mm, and the bed height of T1 is 1840 mm; take catalyst A and inert magnetic rings at a volume ratio of 2:1 to dilute and compound to form T2, and load it into the tube array, and the bed height of T2 is 1830 mm; take catalyst A and inert magnetic rings at a volume ratio of 1:1 to dilute and compound to form T3, and load it into the tube array, and the bed height of T3 is 1830 mm; the ratio of the bed height of T1, the bed height of T2 and the bed height of T3 is 1:1:1, and the total bed height is 5500 mm. The catalytic performance is evaluated and tested, and the test result A9 is obtained.

[0033] Example 10: Take catalyst A as T1 and load it into a tube array with a tube length of 7000 mm, and the bed height of T1 is 3000 mm; take catalyst A and inert magnetic rings in a volume ratio of 1:1 and dilute and compound to form T2, which is loaded into the tube array, and the bed height of T2 is 3000 mm; the ratio of the bed height of T1 to the bed height of T2 is 1:1, and the total bed height is 6000 mm. The catalytic performance is evaluated and tested, and the test result A10 is obtained.

[0034] Example 11: Take catalyst A as T1 and load it into a tube array with a tube length of 7000 mm, and the bed height of T1 is 3000 mm; take catalyst A and inert magnetic rings in a volume ratio of 2:1 and dilute and compound to form T2, which is loaded into the tube array, and the bed height of T2 is 3000 mm; the ratio of the bed height of T1 to the bed height of T2 is 1:1, and the total bed height is 6000 mm. The catalytic performance is evaluated and tested, and the test result A5 is obtained.

[0035] Example 12: Take catalyst A as T1 and load it into a tube array with a tube length of 7000 mm, and the bed height of T1 is 4000 mm; take catalyst A and inert magnetic rings in a volume ratio of 1:1 and dilute and compound to form T2, which is loaded into the tube array, and the bed height of T2 is 2000 mm; the ratio of the bed height of T1 to the bed height of T2 is 2:1, and the total bed height is 6000 mm. The catalytic performance is evaluated and tested to obtain test result A12.

[0036] Example 13: Take catalyst A as T1 and load it into a tube array with a tube length of 7000 mm, and the bed height of T1 is 4000 mm; take catalyst A and inert magnetic rings in a volume ratio of 2:1 and dilute and compound to form T2, which is loaded into the tube array, and the bed height of T2 is 2000 mm; the ratio of the bed height of T1 to the bed height of T2 is 2:1, and the total bed height is 6000 mm. The catalytic performance is evaluated and tested, and the test result A13 is obtained.

[0037] Example 14: Take catalyst A as T1 and load it into a tube array with a tube length of 7000 mm, and the bed height of T1 is 3000 mm; take catalyst A and inert magnetic rings at a volume ratio of 2:1 to dilute and compound to form T2, and load it into the tube array, and the bed height of T2 is 1500 mm; take catalyst A and inert magnetic rings at a volume ratio of 1:1 to dilute and compound to form T3, and load it into the tube array, and the bed height of T3 is 1500 mm; the ratio of the bed height of T1, the bed height of T2 and the bed height of T3 is 2:1:1, and the total bed height is 6000 mm. The catalytic performance is evaluated and tested, and the test result A14 is obtained.

[0038] Example 15: Take catalyst A as T1 and load it into a tube array with a tube length of 7000 mm, and the bed height of T1 is 2000 mm; take catalyst A and inert magnetic rings at a volume ratio of 2:1 to dilute and compound to form T2, and load it into the tube array, and the bed height of T2 is 2000 mm; take catalyst A and inert magnetic rings at a volume ratio of 1:1 to dilute and compound to form T3, and load it into the tube array, and the bed height of T3 is 2000 mm; the ratio of the bed height of T1, the bed height of T2 and the bed height of T3 is 1:1:1, and the total bed height is 6000 mm. The catalytic performance is evaluated and tested, and test result A15 is obtained.

[0039] Example 16: Take catalyst A as T1 and load it into a tube array with a tube length of 7000 mm, and the bed height of T1 is 3100 mm; take catalyst A and inert magnetic rings in a volume ratio of 1:1 and dilute and compound to form T2, which is loaded into the tube array, and the bed height of T2 is 3100 mm; the ratio of the bed height of T1 to the bed height of T2 is 1:1, and the total bed height is 6200 mm. The catalytic performance is evaluated and tested, and the test result A16 is obtained.

[0040] Example 17: Take catalyst A as T1 and load it into a tube array with a tube length of 7000 mm, and the bed height of T1 is 3100 mm; take catalyst A and inert magnetic rings at a volume ratio of 2:1 and dilute and compound to form T2, which is loaded into the tube array, and the bed height of T2 is 3100 mm; the ratio of the bed height of T1 to the bed height of T2 is 1:1, and the total bed height is 6200 mm. The catalytic performance is evaluated and tested, and the test result A17 is obtained.

[0041] Example 18: Take catalyst A as T1 and load it into a tube array with a tube length of 7000 mm, and the bed height of T1 is 4140 mm; take catalyst A and inert magnetic rings in a volume ratio of 1:1 and dilute and compound to form T2, which is loaded into the tube array, and the bed height of T2 is 2060 mm; the ratio of the bed height of T1 to the bed height of T2 is 2:1, and the total bed height is 6200 mm. The catalytic performance is evaluated and tested, and the test result A18 is obtained.

[0042] Example 19: Take catalyst A as T1 and load it into a tube array with a tube length of 7000 mm, and the bed height of T1 is 4140 mm; take catalyst A and inert magnetic rings at a volume ratio of 2:1 to dilute and compound to form T2, and load it into the tube array, and the bed height of T2 is 2060 mm; the ratio of T1 bed height to T2 bed height is 2:1, and the total bed height is 6200 mm. The catalytic performance is evaluated and tested, and the test result A19 is obtained.

[0043] Example 20: Take catalyst A as T1 and load it into a tube array with a tube length of 7000 mm, and the bed height of T1 is 3100 mm; take catalyst A and inert magnetic rings at a volume ratio of 2:1 to dilute and compound to form T2, and load it into the tube array, and the bed height of T2 is 1550 mm; take catalyst A and inert magnetic rings at a volume ratio of 1:1 to dilute and compound to form T3, and load it into the tube array, and the bed height of T3 is 1550 mm; the ratio of the bed height of T1, the bed height of T2 and the bed height of T3 is 2:1:1, and the total bed height is 6200 mm. The catalytic performance is evaluated and tested, and the test result A20 is obtained.

[0044] Example 21: The example is performed using a catalyst A having an outer diameter of 5.6 mm and a height of 5.6 mm and an inert magnetic ring having an outer diameter of 6.0 mm and a height of 6.0 mm; the catalyst A is taken as T1 and loaded into a tube array with a tube length of 7000 mm, and the bed height of T1 is 2067 mm; the catalyst A and the inert magnetic ring are diluted and compounded in a volume ratio of 2:1 to form T2, which is loaded into the tube array, and the bed height of T2 is 2067 mm; the catalyst A and the inert magnetic ring are diluted and compounded in a volume ratio of 1:1 to form T3, which is loaded into the tube array, and the bed height of T3 is 2066 mm; the ratio of the bed height of T1, the bed height of T2 and the bed height of T3 is 1:1:1, and the total bed height is 6200 mm; the catalytic performance is evaluated and tested, and test result A21 is obtained.

[0045] Examples 22 to 26: Based on Example 21, the examples are performed with the specifications of catalyst A and inert magnetic ring as variables, as follows: Example 22: The implementation process is the same as that of Example 21; the difference is: in this example, the outer diameter of catalyst A in T1 is 5.6 mm, and the height is 5.6 mm; the outer diameter of the inert magnetic ring in T2 is 6.0 mm, and the height is 6.0 mm; the outer diameter of catalyst A in T2 is 5.6 mm, and the height is 5.6 mm; the outer diameter of the inert magnetic ring in T3 is 6.0 mm, and the height is 6.0 mm; the outer diameter of catalyst A in T3 is 5.6 mm, and the height is 5.6 mm; the catalytic performance is evaluated and tested, and test result A22 is obtained.

[0046] Example 23: The implementation process is the same as that of Example 21; the difference is: in this example, the outer diameter of catalyst A in T1 is 5.6 mm, and the height is 5.6 mm; the outer diameter of the inert magnetic ring in T2 is 6.0 mm, and the height is 6.0 mm; the outer diameter of catalyst A in T2 is 6.0 mm, and the height is 6.0 mm; the outer diameter of the inert magnetic ring in T3 is 6.0 mm, and the height is 6.0 mm; the outer diameter of catalyst A in T3 is 6.0 mm, and the height is 6.0 mm; the catalytic performance is evaluated and tested, and test result A23 is obtained.

[0047] Example 24: The implementation process is the same as that of Example 21; the difference is: in this example, the outer diameter of catalyst A in T1 is 6.0 mm, and the height is 6.0 mm; the outer diameter of the inert magnetic ring in T2 is 5.6 mm, and the height is 5.6 mm; the outer diameter of catalyst A in T2 is 5.6 mm, and the height is 5.6 mm; the outer diameter of the inert magnetic ring in T3 is 5.6 mm, and the height is 5.6 mm; the outer diameter of catalyst A in T3 is 5.6 mm, and the height is 5.6 mm; the catalytic performance is evaluated and tested, and test result A24 is obtained.

[0048] Example 25: The implementation process is the same as that of Example 21; the difference is: in this example, the outer diameter of catalyst A in T1 is 6.0 mm, and the height is 6.0 mm; the outer diameter of the inert magnetic ring in T2 is 6.0 mm, and the height is 6.0 mm; the outer diameter of catalyst A in T2 is 5.6 mm, and the height is 5.6 mm; the outer diameter of the inert magnetic ring in T3 is 6.0 mm, and the height is 6.0 mm; the outer diameter of catalyst A in T3 is 5.6 mm, and the height is 5.6 mm; the catalytic performance is evaluated and tested, and test result A25 is obtained.

[0049] Example 26: The implementation process is the same as that of Example 21; the difference is: in this example, the outer diameter of catalyst A in T1 is 6.0 mm, and the height is 6.0 mm; the outer diameter of the inert magnetic ring in T2 is 6.0 mm, and the height is 6.0 mm; the outer diameter of catalyst A in T2 is 6.0 mm, and the height is 6.0 mm; the outer diameter of the inert magnetic ring in T3 is 6.0 mm, and the height is 6.0 mm; the outer diameter of catalyst A in T3 is 6.0 mm, and the height is 6.0 mm; the catalytic performance is evaluated and tested, and test result A26 is obtained.

[0050] Examples 27-28: Based on Example 21, catalyst B and catalyst C are used to replace catalyst A to perform the examples, as follows: Example 27: The implementation process is the same as that of Example 21, except that catalyst B (compared with catalyst A, magnesium carbonate is not introduced) is used to replace catalyst A. In this example, the preparation process of catalyst B is as follows: (1) In a glass reactor in the laboratory, 2500 g of isobutyl alcohol, 500 g of benzyl alcohol, and 417 g of vanadium pentoxide are added in sequence, the stirred reactor is started, stirred and heated, and the temperature is controlled to be 120°C. After the temperature reaches the required temperature, 490 g of phosphoric acid is added at a uniform speed. The phosphoric acid is added within 1 hour, and then The reactor was then opened for reflux, and the reflux reaction time was 20 hours. After the reaction was completed, the temperature was lowered and filtered to obtain a filter cake, which was then dried at 100°C for 18 hours; the filter cake was calcined at 300°C for 6 hours to obtain an active precursor; (2) the active precursor was granulated, sieved through a 40-mesh sieve, mixed with 3% graphite, and pressed into tablets. The sample was activated at 460°C in an atmosphere furnace with an oxygen content of 12% for 18 hours, and then cooled to obtain a catalyst B; its catalytic performance was evaluated and tested, and the test result A27 was obtained.

[0051] Example 28: The implementation process is the same as that of Example 21, except that: Catalyst C (compared with Catalyst A, antimony oxide / graphene is introduced) is used to replace Catalyst A. In this example, the preparation process of Catalyst C is as follows: (1) In a glass reactor in the laboratory, 2500 g of isobutyl alcohol, 500 g of benzyl alcohol, 417 g of vanadium pentoxide, 19.5 g of magnesium carbonate, and 4.17 g of antimony oxide are added in sequence, the stirred reactor is started, stirred and heated, and the temperature is controlled to be 120°C. After the temperature reaches the required level, 490 g of phosphoric acid is added at a uniform rate for 1 hour. After phosphoric acid is added, the reactor is opened for reflux for 20 hours. After the reaction is completed, the temperature is lowered and filtered to obtain a filter cake, which is then dried at 100°C for 18 hours; the filter cake is calcined at 300°C for 6 hours to obtain an active precursor; (2) the active precursor is granulated, sieved through a 40-mesh sieve, mixed with 3 wt% of graphite, pressed into tablets, and activated in an atmosphere furnace with an oxygen content of 12% at a controlled temperature of 460°C for 18 hours, cooled, and a catalyst C is obtained; its catalytic performance is evaluated and tested, and the test result A28 is obtained.

[0052] All relevant test data in the above embodiments are shown in the following table:

[0053] Conclusion: From the data in the above table, it can be seen that: in the scheme, the butane process maleic anhydride catalyst prepared by introducing a catalytic metal salt into catalyst A and combining it with an inert magnetic ring has the advantages of high load and low resistance, and can be applied to multi-stage beds; at the same time, the data from Examples 27 to 28 show that: in Example 27, since magnesium carbonate was not introduced, the overall performance of the catalyst changed and the catalytic activity decreased; in Example 28, antimony oxide / graphene was further introduced to effectively improve the catalytic selectivity and catalytic activity.

[0054] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a multi-stage bed high-load low-resistance butane process maleic anhydride catalyst, characterized in that: The following steps are involved: Step 1: (1) adding vanadium pentoxide and a catalytic metal salt to a mixed solvent of isobutyl alcohol and benzyl alcohol in sequence; controlling the temperature to 100-130°C, and uniformly adding phosphoric acid dropwise within 1-2 hours; continuing the reflux reaction for 10-20 hours; cooling and filtering; obtaining a filter cake; (2) drying and calcining the filter cake in sequence to obtain an active precursor; Step 2: (1) granulating the active precursor, adding graphite and mixing evenly, and pressing to form a catalyst A semi-finished product; (2) activating the catalyst A semi-finished product in an oxygen-containing atmosphere to obtain catalyst A; Step 3: dilute and compound the catalyst A with an inert magnetic ring to obtain a butane-process maleic anhydride catalyst.

2. The method for preparing a multi-stage bed high-load low-resistance butane-based maleic anhydride catalyst according to claim 1, characterized in that: The active precursor includes the following raw materials by weight: 400-420 parts of vanadium pentoxide, 18-20 parts of a catalytic metal salt, 2400-2600 parts of isobutanol, 480-500 parts of benzyl alcohol, and 480-500 parts of phosphoric acid; The metal type of the catalytic metal salt includes at least one of magnesium, aluminum and calcium.

3. The method for preparing a multi-stage bed high-load low-resistance butane-based maleic anhydride catalyst according to claim 1, characterized in that: The dilution and compounding ratio between catalyst A and inert magnetic ring is 1:1~2:

1.

4. The method for preparing a multi-stage bed high-load low-resistance butane-based maleic anhydride catalyst according to claim 1, characterized in that: In step 1 (2), the specific process is: drying the filter cake at 100-130° C. for 18 hours, and then calcining at 300-350° C. for 6 hours to obtain an active precursor.

5. The method for preparing a multi-stage bed high-load low-resistance butane-based maleic anhydride catalyst according to claim 1, characterized in that: In the catalyst A semi-finished product, the added amount of graphite accounts for 2-5wt% of the catalyst A semi-finished product.

6. The method for preparing a multi-stage bed high-load low-resistance butane-based maleic anhydride catalyst according to claim 1, characterized in that: The particle size of the active precursor granulation is 10-40 mesh; the catalyst A is a hollow cylinder with an outer diameter of 5-7 mm, a height of 5-7 mm, and an inner diameter of 2.5-4 mm.

7. The method for preparing a multi-stage bed high-load low-resistance butane-based maleic anhydride catalyst according to claim 1, characterized in that: In step 2 (2), the specific process is: placing the semi-finished product of catalyst A in an atmosphere with an oxygen content of 10% to 14%, controlling the temperature to 460 to 480° C. and activating for 10 to 18 hours; obtaining catalyst A.

8. The method for preparing a multi-stage bed high-load low-resistance butane-based maleic anhydride catalyst according to claim 1, characterized in that: Antimony oxide / graphene is added to the active precursor; the specific process includes the following steps: (1) adding vanadium pentoxide and a catalytic metal salt to a mixed solvent of isobutyl alcohol and benzyl alcohol in sequence; adding antimony oxide / graphene and dispersing them evenly; controlling the temperature to 100-130° C. and uniformly adding phosphoric acid dropwise within 1-2 hours; continuing the reflux reaction for 10-20 hours; cooling and filtering to obtain a filter cake; (2) drying and calcining the filter cake in sequence to obtain an active precursor; The added amount of antimony oxide / graphene accounts for 0.8-1wt% of vanadium pentoxide.

9. The method for preparing a multi-stage bed high-load low-resistance butane-based maleic anhydride catalyst according to claim 8, characterized in that: The preparation method of antimony oxide / graphene is as follows: (1) dissolving yttrium nitrate and antimony trichloride in anhydrous ethanol at a molar ratio of 1:8-12 respectively to obtain yttrium solution and antimony solution; dropping the yttrium solution into the antimony solution, stirring evenly, adding ammonia water, adjusting the pH value to 7-10 with acid, stirring at room temperature for 2-4 hours; filtering, washing, and drying; The antimony oxide is calcined at 300-600°C for 2-3 hours to obtain antimony oxide; (2) the antimony oxide is ultrasonically dispersed in ethylene glycol, and graphene oxide is added and stirred evenly; the antimony oxide is subjected to hydrothermal reaction at 120-140°C for 8-12 hours, and then washed, dried and ground to obtain antimony oxide / graphene; wherein the mass ratio of antimony oxide to graphene oxide is 1:3-5.

10. A butane process maleic anhydride catalyst prepared according to the method for preparing a multi-stage bed high-load low-resistance butane process maleic anhydride catalyst according to any one of claims 1 to 9.